De 'Langreuter' melkmachine: reconstructie van een doodlopende ontwikkeling - Nederbragt, Bert; Aarts, Babke (Studium, 2017)
The ‘Langreuter’ Milking Machine: Reconstruction of a Dead-EndThis paper describes the place of the Langreuter milking machine in the development of machine milking between 1890 and 1915. The machine is stored in the depot of the University Museum in Utrecht, the Netherlands. It is a pressure roller machine, working according to the principle of imitating hand milking; this type of machine lost the competition in the development of automated milking practice in favour of vacuum milking. In addition to material examination of the museum object, we used archives, reports and patents to reconstruct the history and working of the machine. Reports of the functioning of pressure rollers show that they worked well with regard to milk production and quality, but that they did not fit the udders of all cows, which may have contributed to their loss of a place in the market. Our own investigations in a milking parlour with modern cows confirmed this.